A Single Swede Midge (Diptera: Cecidomyiidae) Larva Can Render Cauliflower Unmarketable. Issue 3 (19th June 2018) - Stratton, Chase A; Hodgdon, Elisabeth A; Zuckerman, Samuel G; Shelton, Anthony M; Chen, Yolanda H
Abstract: Swede midge, Contarinia nasturtii Kieffer (Diptera: Cecidomyiidae), is an invasive pest causing significant damage on Brassica crops in the Northeastern United States and Eastern Canada. Heading brassicas, like cauliflower, appear to be particularly susceptible. Swede midge is difficult to control because larvae feed concealed inside meristematic tissues of the plant. In order to develop damage and marketability thresholds necessary for integrated pest management, it is important to determine how many larvae render plants unmarketable and whether the timing of infestation affects the severity of damage. We manipulated larval density (0, 1, 3, 5, 10, or 20) per plant and the timing of infestation (30, 55, and 80 d after seeding) on cauliflower in the lab and field to answer the following questions: 1) What is the swede midge damage threshold? 2) How many swede midge larvae can render cauliflower crowns unmarketable? and 3) Does the age of cauliflower at infestation influence the severity of damage and marketability? We found that even a single larva can cause mild twisting and scarring in the crown rendering cauliflower unmarketable 52% of the time, with more larvae causing more severe damage and additional losses, regardless of cauliflower age at infestation.